2016
DOI: 10.3402/ejpt.v7.29295
|View full text |Cite
|
Sign up to set email alerts
|

Trauma research in the Baltic countries: from political oppression to recovery

Abstract: The aim of this paper is to provide an overview of traumatic stress studies from the three Baltic countries—Lithuania, Latvia, and Estonia—and reveal how specific social context contributes to the topics relevant in traumatic stress field in the region. Traumatic stress studies in the Baltic countries are closely related to the complicated history of the region. It was only since the restoration of independence of the Baltic States in the 1990s when traumatic stress studies could emerge. The start of the psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 19 publications
2
22
0
2
Order By: Relevance
“…Threat symptoms specifically predicted current self‐perceived social acknowledgment as a survivor. In Germany and other former communist countries in Eastern Europe, many former political prisoners of the totalitarian regime still feel unacknowledged (Kazlauskas & Zelviene, ). Current results indicate that their ongoing sense of threat may have a substantial social component and not only consists of reactions towards situational or other contextual triggers.…”
Section: Discussionmentioning
confidence: 99%
“…Threat symptoms specifically predicted current self‐perceived social acknowledgment as a survivor. In Germany and other former communist countries in Eastern Europe, many former political prisoners of the totalitarian regime still feel unacknowledged (Kazlauskas & Zelviene, ). Current results indicate that their ongoing sense of threat may have a substantial social component and not only consists of reactions towards situational or other contextual triggers.…”
Section: Discussionmentioning
confidence: 99%
“…General population studies reveal high levels of trauma exposure (Kazlauskas & Zelviene, 2016), although recent analyses of health care data showed that only about 1% of probable PTSD cases are diagnosed (Kazlauskas, Zelviene, & Eimontas, 2017). Problems in diagnosing stress-related disorders could be attributed to lack of health care resources (Kazlauskas & Zelviene, 2016), and to limited knowledge about PTSD among health professionals. However, underdiagnosing of PTSD in Lithuania could also indicate a different symptom profile in the Lithuanian population exemplifying the need for cross-cultural validation of ICD-11 proposals.…”
Section: Introductionmentioning
confidence: 99%
“…From 1918 to 1940 Lithuania was an independent country; in 1990 its independence was restored, ending the Soviet regime's almost 50-year-long occupation. Lithuania joined the EU in 2004 (Kazlauskas & Zelviene, 2016).…”
mentioning
confidence: 99%
“…There is a lack of epidemiological data on the prevalence of PTSD in the Baltic countries (Kazlauskas & Zelviene, 2016); however, a few studies have reported PTSD prevalence in Lithuania ranging from 2% to 6% in several studies (Bunevicius et al, 2014;Domanskaité-Gota, Elklit, & Christiansen, 2009). Furthermore, there is no data on how often PTSD is identified in the health care systems in these countries.…”
mentioning
confidence: 99%